Bubble growth and movement in drying paint films. (12th May 2016) - Saranjam, Nazli; Chandra, Sanjeev
Abstract: Paint films with uniform thickness were applied on stainless steel and glass substrates using a model paint consisting of a resin dissolved in butanol. Tests were also done using glycerin–butanol solutions that were as viscous as paint but did not harden after drying. Small air bubbles were introduced into the liquid and test samples cured in a natural convection oven at temperatures varying from of 100–140 °C. Relatively thick (1 mm) paint layers were used in experiments to allow large bubbles to grow that were easy to observe. Photographs of the liquid film surfaces were taken during drying and weight loss was measured. Cellular structures appeared in drying paint films, induced by surface tension gradients. Small bubbles were transported from the centers to the edges of the cells formed in the liquid layer. Bubbles grew larger as the evaporating solvent diffused into them and were drawn towards each other, forming clusters. Analytical solutions of the mass-diffusion equation were used to model solvent evaporation from the paint film surface, calculate the magnitude of concentration gradients, and estimate bubble growth rates. Highlights: Two various mechanisms were investigated for bubble clustering in binary mixtures. Bubble migration and clustering relies on Marangoni convection and/or buoyancy. Bubble growth rate was initially slow, as predicted by an analytical model. Bubbles growth rate increased, due to super-saturation of the paint with solvent. Super-saturation of paint layer was connected with "skinning" at the surface. Clustering of larger bubbles was driven by buoyancy forces, in later stages of curing.